Merchant Education and Digital Marketing Guidance for SM Snacks and Ribs Corner in Salatiga City - Gunarto, Alexandra Nesta Levina; Ardana, Alfario David; Fevriera, Sotya; Pertiwi, Angelita Titis; Putri, Christina Ari Pramono (Bakti Cendana, 2026)
This community service activity aims to provide digital marketing training to traders mentored by the Trade Office of Salatiga, offer digital marketing assistance, and create a minimum of 3 digital marketing contents for 2 traders fostered by the Trade Office of Salatiga. This activity was carried out in 3 stages (training, socialization, and mentoring). Digital marketing training activities have been done for all traders fostered by the Salatiga Trade Office. The socialization of mentoring activities was carried out through WhatsApp chat, and then followed up by visiting traders who responded positively. The results of the mentoring successfully encouraged the SM Snacks owner to try digital marketing using Business WhatsApp, and the manager of the Ribs Corner food outlet wanted to try the boost feature on her Business Instagram. Community service activities also help complement SM's Business WhatsApp snack with product catalog features, Anyflip-based digital catalog, and promotional posters, as well as creating 2 video contents to be uploaded to the Ribs Corner business Instagram. Because the team in the mentoring process has developed two social medias, each with minimum of 2 contents for two traders, then it can be concluded that the team has achieved the objectives of the activity.